Kajian Literatur: Peran Media Sosial Dalam Pemasaran Secara Komprehensif - Nurjanah, Anisa; Ananda, Nadya Asri; Azqia, Syifa; Hananto, Djoko (Philosophiamundi, 2024)
This study delves into the role played by social media in contemporary marketing strategies. With the ever-expanding landscape of information and communication technology, social media has emerged as a primary platform for companies to engage with their consumers. The research aims to identify how social media influences consumer behavior, creates brand awareness, enhances customer engagement, and ultimately impacts purchase decisions. Research methods employed include surveys, interviews, and data analysis. Findings indicate that social media not only serves as a means to promote products or services but also as a vital platform for fostering closer relationships between brands and consumers. The practical implications underscore the importance of integrated marketing strategies with social media in this digital era. In conclusion, a profound understanding of the role of social media in marketing can offer valuable insights for practitioners and researchers in developing effective marketing strategies for the future.